New Protein-Coated Silver Nanoparticles: Characterization, Antitumor and Amoebicidal Activity, Antiproliferative Selectivity, Genotoxicity, and Biocompatibility Evaluation - Lucía Margarita Valenzuela-Salas; Alberto Blanco-Salazar; Jesús David Perrusquía-Hernández; Mario Nequiz-Avendaño; Paris A. Mier-Maldonado; Balam Ruiz-Ruiz; Verónica Campos-Gallegos; María Evarista Arellano-García; Juan Carlos García-Ramos; Alexey Pestryakov; Luis Jesús Villarreal-Gómez; Yanis Toledano-Magaña; et al. (MDPI AG, 2021)
Nanomaterials quickly evolve to produce safe and effective biomedical alternatives, mainly silver nanoparticles (AgNPs). The AgNPs' antibacterial, antiviral, and antitumor properties convert them into a recurrent scaffold to produce new treatment options. This work reported the full characterization of a highly biocompatible protein-coated AgNPs formulation and their selective antitumor and amoebicidal activity. The protein-coated AgNPs formulation exhibits a half-inhibitory concentration (IC50) = 19.7 µM (2.3 µg/mL) that is almost 10 times more potent than carboplatin (first-line chemotherapeutic agent) to inhibit the proliferation of the highly aggressive human adenocarcinoma HCT-15. The main death pathway elicited by AgNPs on HCT-15 is apoptosis, which is probably stimulated by reactive oxygen species (ROS) overproduction on mitochondria. A concentration of 111 µM (600 µg/mL) of metallic silver contained in AgNPs produces neither cytotoxic nor genotoxic damage on human peripheral blood lymphocytes. Thus, the AgNPs formulation evaluated in this work improves both the antiproliferative potency on HCT-15 cultures and cytotoxic selectivity ten times more than carboplatin. A similar mechanism is suggested for the antiproliferative activity observed on HM1-IMSS trophozoites (IC50 = 69.2 µM; 7.4 µg/mL). There is no change in cell viability on mice primary cultures of brain, liver, spleen, and kidney exposed to an AgNPs concentration range from 5.5 µM to 5.5 mM (0.6 to 600 µg/mL). The lethal dose was determined following the OECD guideline 420 for Acute Oral Toxicity Assay, obtaining an LD50 = 2618 mg of Ag/Kg body weight. All mice survived the observational period; the histopathology and biochemical analysis show no differences compared with the negative control group. In summary, all results from toxicological evaluation suggest a Category 5 (practically nontoxic) of the Globally Harmonized System of Classification and Labelling of Chemicals for that protein-coated AgNPs after oral administration for a short period and urge the completion of its preclinical toxicological profile. These findings open new opportunities in the development of selective, safe, and effective AgNPs formulations for the treatment of cancer and parasitic diseases with a significant reduction of side effects.